Elastic modulus evolution of rocks under heating–cooling cycles - Liu, Weidong; Zhang, Liangchi; Luo, Ning (Scientific reports, 2020)
Rocks decay significantly during or after heating–cooling cycles, which can in turn lead to hazards such as landslide and stone building collapse. Nevertheless, the deterioration mechanisms are unclear. This paper presents a simple and reliable method to explore the mechanical property evolutions of representative sandstones during heating–cooling cycles. It was found that rock decay takes place in both heating and cooling processes, and dramatic modulus changes occurred near the α − β phase transition temperature of quartz. Our analysis also revealed that the rock decay is mainly attributed to the internal cracking. The underlying mechanism is the heterogeneous thermal deformation of mineral grains and the α – β phase transition of quartz.